STUDIA NAD STRATYGRAFIĄ I POZIOMAMI ARCHITEKTONICZNO-UŻYTKOWYMI ZAMKU KRUSZWICKIEGO - Pawlak, Piotr (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2021)
The castle in Kruszwica was built after 1343, at the request of Casimir III the Great. The oldest written sources, Kronika by Jan of Czarnków, dates the construction of the castle back to 1350-1355. The castle hosted the seat of the starost, judiciary authorities and a prison. In 1973-1982, the excavations were located in the central and south-western parts of the Castle Hill. In 2007-2008, the archaeological excavations were moved to the crests of the Hill; in 2010-2011 they were located chiefly near the structures of the castle building, still uncovered in 1973-1982. As a result, relics of the castle house were excavated together with several cellar rooms and fragments of the peripheral wall with remains of a gate. Following the results of stratigraphic and architectural analyses, the results of the research into the movable historic material, coupled with the results of 14C radiocarbon dating, four chronological periods have been identified in the history of the castle in Kruszwica: period I – since the mid-14th c. to 1519; period II – after 1519 to 1591; period III – after 1591 to 1657; period IV – after 1657.